PLTS Hybrid Modeling with Vertical Wind Power - I Ketut Parti; I Made Sumertayasa; Ni W Rasmini (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
The current energy crisis has once again taught us, the people of Indonesia, that serious and systematic efforts to develop and implement renewable energy sources to reduce dependence on fuel must be carried out immediately. The use of renewable and environmentally friendly energy sources, especially those that can reduce the various adverse effects caused by the use of fossil fuels. The urge to leave petroleum as a source of national energy supply is currently being rolled out by various parties, including themselves. These steps are needed to get Indonesia out of the sustainable energy crisis. To optimize the need to combine two generators, namely PLTS with PLTB. The purpose of this study was to determine the combination of a power generation system produced by a vertical wind power plant with solar power with a hybrid system which is expected to optimize the power generation system between the two plants.